Fast, highly enantioselective, and sustainable fluorination of 4-substituted pyrazolones catalyzed by amide-based phase-transfer catalysts. Issue 9 (3rd April 2023) - Wang, Yakun; Wang, Shuaifei; Wu, Yufeng; Zhao, Ting; Liu, Jie; Zheng, Junlin; Wang, Lin; Lv, Jieli; Zhang, Tao
Abstract : Highly enantioselective and sustainable fluorination of 4-substituted pyrazolones has been developed by amide-based phase-transfer catalysts. Abstract : We developed the amide-based Cinchona alkaloids-catalyzed enantioselective fluorination of 4-substituted pyrazolones; the products with tetrasubstituted fluorine-attached chiral center were afforded in high yields (up to 99%) with excellent enantioselectivities (up to 98% ee). Our method is highlighted by low catalyst loading (0.05–0.5 mol%), short reaction times (30 minutes) and broad substrate scopes (35 examples). Furthermore, we carried out this asymmetric fluorination under sustainable conditions in 10 cycles, and the optically pure product (>99.5% ee) could be easily obtained by simple extraction and recrystallization on a multigram scale. Controlled experiments and DFT studies showed that the multiple hydrogen bonding interactions and the steric hindrance at the ortho -position in the benzene ring of the catalyst were the main reasons for the high enantioselectivity and reactivity. With a simple operational protocol and low catalyst loading, this transformation provides a practical method for the preparation of chiral fluorine-containing compounds.